Pengaruh Pemberian Beberapa Formula Pupuk untuk Peningkatan Produksi dan Mutu Sawi Hijau (brassica juncea l.) di Tanah Inceptisol, Desa Pegok, Denpasar - PURBA, IRNAWATI; LANYA, INDAYATI; SUPADMA, A.A. NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
The Impact Of Several Fertilizer Formula For IncreaseTheProduction and Quality Of Green Mustard (Brassica juncea L.) in Inceptisol Soil, Pegok Village, Denpasar This research aims to know the impact of several fertilizer formulas towards production and quality increase of green mustard in inceptisol soil, and the chemical characters of Pegok land. This research was conducted in September until December 2015 at the Experimental Garden Faculty of Agriculture, and Soil Laboratory and Environmental Sciences, Faculty of Agriculture, Udayana University. The experiment used Randomized Block Design (RBD) and the using analysis of variance (ANOVA) with program Costat. The parameter observed in this research was divided into three observations, they were the height of plants, the weight of fresh plants sample, the weight of fresh plants. The plants quality contains of chlorophil, water content and plants storability. The observartion of chemical characters of the plants encompasses pH, KTK, KB, nutrient content N-total, P- available, K-available, Ca, Mg, C-Organic, as well as soil electric conductivity. The result of statistical analysis shows that giving some fertilizer formulas has significant impact for all production and quality parameter namely leaf chlorophyll however does not give real impact towards water content and plants storability. The impact of giving some fertilizer formulasfor mineral fertilizer treatment increase the residual effect of several nutrient contents namely Ca, Mg, pH and highest DHL, whilst KTK, KB, C-organic and highest N-Total were obtained from the organic fertilizer treatment.
Keywords: Green Mustard; fertilization; inceptisol